A preliminary report of incidence of divorce among Indian Muslims - Ibn-i Farīd, 1925-2003.; Institute of Objective Studies (New Delhi, India) (New Delhi : The Institute : Marketed by Qazi Publishers & Distributors, 1996)
Study conducted in Aligarh and Delhi cities.
Includes bibliographical references and index.
Keywords: Divorce -- India; Muslim women -- India -- Social conditions